Broadband all-metal Vivaldi antenna with Rexolite inserted slot edge - Ari, Onur; Kizilay, Ahmet (WILEY, 2022)
In this study, broadband, with a reconfigurable pattern, a slot edge all-metal Vivaldi antenna (SEMVA) is proposed. The designed antenna is fabricated from an aluminum plate. Then the antenna is measured in an anechoic chamber using a spherical near field measurement system. In the first step, the metal Vivaldi antenna without slots is designed as a reference model. The scattering parameters and the radiation pattern results show that the antenna exhibits poor vswr and deteriorated radiation patterns at the lower operating band. In order to overcome these performance problems, the slot edge technique is successfully adapted to the metal Vivaldi antenna. This technique provides wider bandwidth with vswr <2 and a directive radiation pattern at lower operating frequencies. The dielectric material (Rexolite) can also be inserted into the slots of the designed antenna to improve bandwidth and beamwidth. The proposed antennas with and without dielectric insertion are measured and compared. The measurement results show that using slots increase the bandwidth of the designed antenna from 6:1 to 10:1. The proposed antenna operates between 1.38 and 13.8 GHz with a proper end-fire radiation pattern. In addition, the power handling capacity of the SEMVA is calculated and compared with PCB antennas.
Keywords: all-metal Vivaldi antennas; antenna power handling; broadband antennas; reconfigurable pattern; tapered slot antennas; Vivaldi antennas; ARRAY ANTENNA; DESIGN; Engineering; Optics